A general optimal adaptive framework for managing a threatened species. Issue 4 (20th October 2022) - Nicol, Sam; Ferrer‐Mestres, Jonathan; Lloyd, Hannah; Brazill‐Boast, James; Gorrod, Emma; Chades, Iadine
Abstract: Managers must determine which interventions best protect threatened species when the outcomes of interventions are uncertain. Adaptive management is a dynamic optimization approach that generates optimal management actions based on current knowledge while learning to improve future management outcomes. Although adaptive management theory is well‐developed, uptake has been impeded by its complexity and a tendency to develop bespoke solutions with high implementation costs for problem‐specific returns. To increase uptake of adaptive management and improve threat management for species recovery, we developed a general adaptive management decision model, framed as a Mixed Observability Markov Decision process. We embraced principles of generality, simplicity and interpretability to overcome previous implementation challenges. We created a general model structure that is applicable to any species–threat combination, thus avoiding the need to develop customized models for every species. Simplicity was achieved by minimizing states to reduce the information requirements for parameterization. To improve interpretability, we implemented our method as a Shiny application and employed a recent artificial intelligence approach to simplify the optimal strategy. We applied our approach to a case study of fox impacts on a threatened marsupial. Our case study shows that when one management action is robust to uncertainty, the value of information of optimal adaptive management may be low. Cases like these highlight species–threat combinations where investment in adaptive management is not required. Our tool provides a rapid prototype adaptive management approach with minimal cost to management agencies. Our simple yet general model structure improves efficiency for implementing adaptive management for large numbers of threatened species, improving the effectiveness of conservation investments. Abstract : Our general approach to optimise adaptive management for threatened species conservation overcomes multiple existing hurdles to implementation. Our method minimises the information elicited from experts, removes the need to develop custom models for every species and is supported by a Shiny application so users need not interact with specialised solvers. Resumen: Los gestores medioambientales deben determinar que tipo de intervenciones ofrecen mejor protección para las especies amenazadas, aun cuando se desconocen los efectos de estas intervenciones. La gestión adaptativa es un proceso de optimización dinámico que permite generar acciones óptimas basadas en el conocimiento actual de la situación, mientras se aprende a mejorar los resultados de futuras acciones. Aunque la teoría de la gestión adaptativa está bien desarrollada, su adopción se ha visto obstaculizada por su complejidad y por una tendencia a desarrollar soluciones con altos costos de implementación para problemas específicos. Con el fin de incrementar la adopción de la gestión adaptativa y mejorar la gestión de amenazas en la recuperación de especies, hemos desarrollado un modelo de decisión de gestión adaptativa general, enmarcado como un proceso de decisión markoviano de observabilidad mixta (MOMDP). Adoptamos los principios de generalidad, interpretabilidad y simplicidad con el fin de superar los desafíosque supone su implementación. Hemos creado un modelo general que es aplicable a cualquier combinaciónde especie‐amenaza, evitando asíla necesidad de desarrollar modelos específicos para cada especie distinta. La simplicidad se logró minimizando los estados para reducir los requisitos de información para la parametrización del modelo. Con el fin de mejorar la interpretabilidad, hemos implementado nuestro método como una aplicación Shiny y hemos empleado un algoritmo reciente de inteligencia artificial para simplificar la estrategia óptima. Hemos aplicado nuestro método en un caso de estudio sobre el impacto de los zorros en un marsupial amenazado. Nuestro caso de estudio muestra que cuando una acción de gestión es resistentea la incertidumbre, el valor de la información de la gestión adaptativa óptima puede ser bajo. Casos como estos destacan combinaciones de especie‐amenaza donde no se requiere invertir en gestión adaptativa. Nuestra herramienta provee un prototipo rápido de gestión adaptativa con un coste mínimo a las agencias de gestión medioambiental. Nuestro modelo, aunque simple, es general, y mejora la eficiencia al implementar gestión adaptativa en un gran número de especies amenazadas, mejorando la eficacia de las inversiones en conservación.